Teknik Clapping dan Vibrasi Meningkatkan Saturasi Oksigen Pasien PPOK - Ni Made Dwi Yunica Astriani; Kadek Yudi Aryawan; Mochamad Heri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of clapping and vibration on oxygen saturation in COPD patients. The research design used a one-group pre-post test design. The research respondents' results in 26 COPD show the average oxygen saturation values before the intervention was 90.42 into the category of moderate hypoxemia, after a given intervention for two times a day gained an average weight of 95.00 SaO2 SaO2 into the type of standard p-value 0.000. In conclusion, most of them are male, with the lowest age of 31 years, while the respondents' highest period is 60 years. There is an effect of this value, indicating the impact of clapping and vibration on the oxygen saturation of COPD patients. Keywords: Clapping, COPD, Oxygen Saturation, Vibration